2022
DOI: 10.5483/bmbrep.2022.55.8.101
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in studies of biomolecular phase separation.

Abstract: Biomolecular phase separation has recently attracted broad in-terest, due to its role in the spatiotemporal compartmentalization of living cells. It governs the formation, regulation, and dissociation of biomolecular condensates, which play multiple roles in vivo , from activating specific biochemical reactions to organizing chromatin. Interestingly, biomolecular phase separation seems to be a mainly passive process, which can be ex-plained by relatively simple physical principles and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…In some external conditions change, some of the molecules in the multi-component system will be enriched to a specific region of the system, the separation of several phases with different components and structures of the process is called phase separation [ 1 ]. In 2009, Brangwynne et al in their study of the mechanisms of fertilized egg polarization and asymmetric division in Caenorhabditis elegans showed that P granules exhibit liquid-like phase change behavior, including fusion, dropping, and wetting [ 2 ].…”
Section: The Formation Of Phase Separation and The Factors Affecting ...mentioning
confidence: 99%
“…In some external conditions change, some of the molecules in the multi-component system will be enriched to a specific region of the system, the separation of several phases with different components and structures of the process is called phase separation [ 1 ]. In 2009, Brangwynne et al in their study of the mechanisms of fertilized egg polarization and asymmetric division in Caenorhabditis elegans showed that P granules exhibit liquid-like phase change behavior, including fusion, dropping, and wetting [ 2 ].…”
Section: The Formation Of Phase Separation and The Factors Affecting ...mentioning
confidence: 99%
“…This review is by no means a complete and thorough review of the field; interested readers may be referred to fuller reviews. [11][12][13][14][15][16][17][18][19] This review rather aims to provide a brief sketch of the field. We start our discussion with a summary of what biomolecular phase separation is.…”
Section: Introductionmentioning
confidence: 99%
“…As a short addendum, we also discuss recent advances in machine‐learning‐based methods to study biomolecular phase separation. This review is by no means a complete and thorough review of the field; interested readers may be referred to fuller reviews 11–19 . This review rather aims to provide a brief sketch of the field.…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, LLPS is driven by both intraand intermolecular interactions [8], including π-π stacking, cation-π, and electrostatic interactions, among residues termed "stickers" [9]. Conversely, "spacers" elements, such as Gly and polar amino acids, serve to separate sticker residues, facilitating the formation of optimal LLPS interactions [10]. Collectively, sequence-specific motifs and chemical context synergistically govern LLPS [11].…”
Section: Introductionmentioning
confidence: 99%